Potensi Financial Distress dengan Metode Grover pada Bank Digital yang Terdaftar di Bursa Efek Indonesia Periode 2020-2024 - Ristha Indriani Sukma; Ira Phajar Lestari (JPNM Jurnal Pustaka Nusantara Multidisiplin, 2025)
Digital transformation in Indonesia's banking sector has become an important part of people's lives, especially since the COVID-19 pandemic. Conventional banks, through super apps, have targeted market segments that have been dominated by digital banks, creating direct competition in the digital services arena. Financial instability and intense competition experienced by digital banks increase the risk of financial distress. This study aims to identify and analyze the potential for financial distress in digital banks listed on the IDX during the 2020-2024 period based on the Grover method. The object of this study is financial distress using the Grover method in digital banks. The type of data used is quantitative in the form of financial reports for the 2020-2024 period, and the data source is secondary, obtained by accessing the IDX website and each company. The data collection procedures used are documentation and the Grover method analysis technique. The results and discussion show that PT Bank Amar Indonesia Tbk is in a healthy condition, except in 2021 when it experienced a grey area. PT Bank Jago Tbk was in a healthy condition from 2020 to 2023, but in 2024 it declined to the grey area category. PT Bank Neo Commerce Tbk was in the healthy category in 2020 and in the grey area for three consecutive years, namely 2021 to 2023, but managed to return to the healthy category in 2024.